Uganda : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. (IMF Staff Country Reports; Country Report, 2004)
This paper assesses Uganda's Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. The fiscal program was broadly on track in 2003/04. Performance under the PRGF-supported program was mixed. Despite some slippages, most quantitative performance criteria were observed for December 2003, and there has been progress in the implementation of structural measures. The authorities are requesting waivers for nonobservance of four performance criteria based on corrective actions taken.